High-filler-ratio double-component high-thermal-conductivity epoxy pouring sealant and preparation method thereof
By adding a high proportion of alumina to the E51 epoxy resin and using a viscosity-reducing additive to build a three-dimensional thermal conductivity mesh chain, the problem of insufficient thermal conductivity of the potting glue is solved, and a two-component epoxy potting glue with high thermal conductivity and suitable viscosity is achieved, which is suitable for new energy vehicle power battery systems.
Patent Information
- Application Number
- CN202510531406.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-08-05
AI Technical Summary
The thermal conductivity of existing potting glues is insufficient, which limits its development in high-end industries such as 5G communications and aerospace. Moreover, the cost of high-thermal potting glues is relatively high, making it difficult to achieve industrial mass production.
By adding a high proportion of alumina to the E51 epoxy resin, a three-dimensional thermal conductivity mesh chain is constructed, and a viscosity reduction additive is added to component B to form a two-component high thermal conductivity epoxy potting adhesive with a high filler ratio to ensure moderate viscosity and achieve self-leveling.
It significantly improves the thermal conductivity of the potting glue, while maintaining appropriate viscosity and storage stability, expanding application scenarios, and is especially suitable for new energy vehicle power battery systems.
Smart Images

Figure CN120424609A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of potting materials, and in particular to a high-filler ratio two-component high-thermal-conductivity epoxy potting adhesive and a preparation method thereof. Background Art
[0002] With the advent of the 5G electronic communication era, electronic products are continuously developing in the direction of integration, complexity, miniaturization and high computing power. As an important component of its assembly and sealing materials, potting compound has broad application prospects. In terms of application trends, thermal conductive potting compound has a wide range of applications, but with the development of the new energy vehicle industry, the application of thermal conductive potting compound has gradually shifted from the field of electronic components to the field of power battery systems. In the future, the market development potential of thermal conductive potting compound for new energy vehicles is huge. Epoxy potting compound has been widely used in the electronic device manufacturing industry because of its high hardness and good gloss of cured product, and its many advantages such as fixation, insulation, waterproofness, oil resistance, corrosion resistance, and aging resistance. Among them, E51 bisphenol A series epoxy resin is an ideal matrix material for epoxy potting compound because of its good insulation performance, chemical corrosion resistance, low curing shrinkage (less than 2%), and low price.
[0003] Currently, the thermal conductivity of potting compounds used primarily in industry is generally insufficient. The thermal conductivity of general-purpose two-component epoxy potting compounds is only around 0.6-0.8W (m / k), limiting their development in high-end industries such as 5G communications and aerospace. While some two-component epoxy potting compounds can achieve a thermal conductivity of 1.5W (m / k) or higher, they are relatively expensive. Research on highly thermally conductive potting compounds is currently focused on composite powder materials (such as Al2O3 / BN); however, considering industrial production efficiency and cost factors, it will take some time for these studies to reach industrial mass production. Summary of the Invention
[0004] In order to solve the above problems, the present invention provides a high filler ratio two-component high thermal conductivity epoxy potting compound and a preparation method thereof, which constructs a high thermal conductivity channel and improves the thermal conductivity of the potting compound.
[0005] To this end, the technical solution of the present invention is: a high filler ratio two-component high thermal conductivity epoxy potting adhesive, composed of independent components A and B in a mass ratio of 2.5:1 to 3.5:1, wherein:
[0006] Component A includes the following components by mass fraction: 9-28 parts of E51 epoxy resin, 0.3-0.7 parts of diluent, 70-90 parts of aluminum oxide, 0.8-1.2 parts of dispersant, and 0.3-0.7 parts of defoaming agent;
[0007] Component B includes the following components by mass fraction: 27-33 parts of polyetheramine curing agent, 9-11 parts of alicyclic amine curing agent, 4.5-5.5 parts of E51 epoxy resin, 0.5-0.6 parts of viscosity reducer, 1.8-2.2 parts of curing accelerator, 1.4-1.6 parts of thixotropic enhancer, 0.5-0.6 parts of defoaming agent, 4.1-4.9 parts of thixotropic powder, 41.4-48.6 parts of carbon black and physical filler.
[0008] On the basis of the above scheme and as a preferred scheme of the above scheme: the A component includes the following components by mass fraction: 10 parts of E51 epoxy resin, 0.5 parts of diluent, 88 parts of aluminum oxide, 1 part of dispersant, and 0.5 parts of defoaming agent.
[0009] On the basis of the above scheme and as a preferred scheme of the above scheme: the B component includes the following components by mass fraction: 30 parts of polyetheramine curing agent, 10 parts of alicyclic amine curing agent, 5 parts of E51 epoxy resin, 0.5 parts of viscosity reducing agent, 2 parts of curing accelerator, 1.5 parts of thixotropic enhancer, 0.5 parts of defoaming agent, 4.5 parts of thixotropic powder, 46 parts of carbon black and physical filler.
[0010] On the basis of the above scheme and as a preferred scheme of the above scheme: the mass ratio of component A to component B is 3:1.
[0011] On the basis of the above scheme and as a preferred scheme of the above scheme: the dispersant is BYK-104S, BYK145 or BYK985; the defoaming agent is Deqian 6800 or BYK024.
[0012] On the basis of the above solution and as a preferred solution of the above solution: the alicyclic amine curing agent is an alicyclic diamine, and the viscosity reducing agent is BYK110.
[0013] On the basis of the above solution and as a preferred solution of the above solution: the curing accelerator is DMP30 or AEP; the thixotropic synergist is VA750B, BYK-R605 or BYK-R607.
[0014] On the basis of the above scheme and as a preferred scheme of the above scheme: the thixotropic powder is H18 silica, M5 silica or organic bentonite, and the physical filler is heavy calcium carbonate.
[0015] Another technical solution of the present invention is: a method for preparing a high filler ratio two-component high thermal conductivity epoxy potting adhesive, comprising the following steps:
[0016] 1) Preparation of component A:
[0017] 1.1) Add 9-28 parts of E51 epoxy resin and 0.3-0.7 parts of diluent into a planetary stirred tank and mix well;
[0018] 1.2) Add 0.8-1.2 parts of dispersant and 0.3-0.7 parts of defoamer and stir at low speed;
[0019] 1.3) Add 70-90 parts of aluminum oxide, disperse evenly at low speed, then start high-speed stirring and start vacuum degassing to obtain component A;
[0020] 2) Preparation of component B:
[0021] 2.1) Add 27-33 parts of polyetheramine curing agent and 9-11 parts of alicyclic amine curing agent into a planetary mixer and heat to above 80°C;
[0022] 2.2) Add 4.5-5.5 parts of E51 epoxy resin and perform a pre-reaction. Take a small amount of the pre-reaction sample for infrared testing. If there is no obvious epoxy characteristic peak, the pre-reaction process is complete.
[0023] 2.3) After the pre-reaction process is completed, add 0.5-0.6 parts of viscosity reducing agent, 1.8-2.2 parts of curing accelerator, 1.4-1.6 parts of thixotropic synergist, and 0.5-0.6 parts of defoamer, and disperse at high speed until no obvious particles are left;
[0024] 2.4) Add 4.1-4.9 parts of thixotropic powder and 41.4-48.6 parts of carbon black and filler, disperse at high speed and start vacuum degassing to obtain component B
[0025] 3) Weigh component A and component B according to a mass ratio of 2.5:1 to 3.5:1, mix them evenly by manual mixing or mechanical stirring, and then use.
[0026] When preparing component A, the present invention adds 70-90% alumina to the E51 epoxy resin. This high proportion of inorganic powder allows the filler to form a three-dimensional thermally conductive network within the resin, creating a highly thermally conductive channel and improving the thermal conductivity of the potting compound. In E51 epoxy potting compound, increasing the thermally conductive powder content significantly increases the viscosity of the system. This is because the addition of inorganic fillers such as metal oxides enhances intermolecular interactions within the system, restricting the movement of molecular segments and leading to increased viscosity. This increased viscosity can affect the performance of the potting compound. Therefore, the maximum thermally conductive powder content in commercially available thermally conductive compounds is only around 50%. Otherwise, the glue will not flow and cannot be used properly.
[0027] The present invention makes the glue into the above component form, and after greatly increasing the aluminum oxide content, causing the viscosity of component A to be too high to flow, a certain amount of viscosity-reducing agent is added to component B. The viscosity-reducing agent can be a copolymer solution containing acidic groups. The acidic groups (such as carboxyl groups, sulfonic acid groups, etc.) in the copolymer solution will dissociate into negatively charged ions in the epoxy potting adhesive system. These negatively charged ions will form a charge layer on the surface of the thermally conductive filler particles, generating electrostatic repulsion. This repulsive force can weaken the van der Waals force between the filler particles, thereby reducing the tendency of the filler particles to agglomerate and reducing the viscosity increase caused by agglomeration.
[0028] Therefore, when adding water, component A and component B are stirred and mixed, and the viscosity reducing agent of component B is used to reduce the viscosity of component A, so that the finished glue can maintain high thermal conductivity and maintain the low viscosity state of the system.
[0029] Compared with the prior art, the present invention has the following beneficial effects: by adding a high proportion of inorganic powder alumina to E51 epoxy resin, the filler forms a three-dimensional heat-conducting network chain in the resin, constructing a high heat-conducting channel, thereby improving the thermal conductivity of the potting compound; in addition, due to the high filler ratio, the product has a higher viscosity, which makes the product have a longer storage period and solves the problem of precipitation of inorganic powder; during use, by mixing and adding component B curing agent, the mixed potting compound has a suitable potting viscosity and can achieve self-leveling. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a structural block diagram of the present invention. DETAILED DESCRIPTION
[0031] Example 1
[0032] The high filler ratio two-component high thermal conductivity epoxy potting adhesive described in this embodiment is composed of independent components A and B, and the mass ratio of the two components is 3:1, wherein:
[0033] Component A consists of the following components, by mass: 10 parts E51 epoxy resin, 0.5 parts diluent, 88 parts alumina, 1 part dispersant, and 0.5 parts defoamer. The diluent is 669 epoxy reactive diluent; the alumina acts as a thermally conductive inorganic powder to improve thermal conductivity; the dispersant is BYK-104S, a solution of a low-molecular-weight unsaturated polycarboxylic acid polymer and a polysiloxane copolymer. The defoamer is 6800, a polysiloxane mixture containing hydrophobic particles.
[0034] The B component includes the following components by mass: 30 parts of polyetheramine curing agent, 10 parts of alicyclic amine curing agent, 5 parts of E51 epoxy resin, 0.5 parts of viscosity reducing agent, 2 parts of curing accelerator, 1.5 parts of thixotropic synergist, 0.5 parts of defoaming agent, 4.5 parts of thixotropic powder, 46 parts of carbon black and physical filler.
[0035] The polyetheramine curing agent is D230, which is used as an epoxy resin curing agent. After curing, it has excellent toughness and fatigue resistance and is widely used in structural adhesives and adhesives.
[0036] The alicyclic amine curing agent is an alicyclic diamine, and PACM (4,4'-diaminodicyclohexylmethane) can be selected; PACM has the characteristics of low viscosity, good color and gloss of the cured product, good weather resistance, and high mechanical strength of the cured product.
[0037] The viscosity-reducing agent, also known as a wetting and dispersing agent, can be BYK-110. This product is a copolymer solution containing acidic groups, which effectively reduces the viscosity of the system while providing excellent wetting and dispersing properties. During the preparation and use of epoxy potting compounds, fillers may reagglomerate due to factors such as mechanical agitation and temperature fluctuations. The acidic groups in the copolymer solution can continuously and stably disperse the filler particles through chemical reactions or physical adsorption on the filler surface, preventing reagglomeration and thus maintaining the system's low viscosity.
[0038] The curing accelerator used is DMP30, chemically known as 2,4,6-tris(dimethylaminomethyl)phenol. Used to accelerate the curing reaction of materials such as epoxy resins, DMP30 can accelerate curing, increase production efficiency, and improve the properties of the cured product, such as increasing its hardness, strength, and chemical resistance.
[0039] The thixotropic synergist selected is VA750B thixotropic synergist, which is composed of higher fatty acid amide. The thixotropic synergist is mainly used to improve the thixotropic properties of the system, that is, it exhibits higher viscosity under static or low shear force, while the viscosity decreases when subjected to high shear force, which helps to prevent precipitation, stratification and other phenomena, and improve the stability and construction performance of the system.
[0040] The thixotropic powder is H18 thixotropic powder, which is composed of hydrophobic silica. The thixotropic powder provides a good thixotropic effect by increasing the structural viscosity of the system, preventing the sedimentation of pigments and fillers, and improving the storage stability and construction performance of products such as coatings and adhesives.
[0041] The physical filler is CA1250, which is composed of heavy calcium carbonate. Carbon black mainly provides color and ultraviolet absorption performance, while heavy calcium carbonate, as a physical filler, is mainly used to reduce costs, adjust the viscosity and hardness of the system, and at the same time improve the wear resistance and covering power of the product.
[0042] The specific preparation method is as follows:
[0043] Step 1: Prepare component A
[0044] Add 10 parts of E51 epoxy resin and 0.5 parts of diluent into a planetary stirring kettle and mix evenly; then add 1 part of dispersant and 0.5 parts of defoamer, stir evenly at low speed, then add 88 parts of alumina, disperse evenly at low speed, then start high-speed stirring and start vacuum defoaming to obtain component A.
[0045] Step 2: Test component A.
[0046] Tested at 25°C:
[0047] ①Viscosity value: Place the test sample into a 1ml centrifuge tube, fix it with a clamp, straighten it, and place it in a water bath. The liquid level should be submerged to 3 / 4 of the centrifuge tube. After standing for 30 minutes, select a suitable rotor and speed for testing.
[0048] ② Flow distance L (use a 10ml syringe, use a utility knife to cut off the needle end to the 2ml scale, move the internal black cap to 6ml, add the colloid into this section of the syringe, align the syringe head with the scale line L0 = 2cm of the fluidity test mold to squeeze out the glue, put it into a constant temperature and humidity chamber at 25℃ / 50%RH, and after 20 minutes, record the total distance L1 of the colloid flow, and then subtract L0; that is: flow distance L = L1-L0; the larger the value, the better the flow of the colloid).
[0049] ③ Sedimentation Degree D [Place the potting compound in a 50ml centrifuge tube at a height of 4cm (at the 20ml mark on the centrifuge tube) in a constant temperature and humidity chamber at 25°C / 50% RH. After 3 days*, slowly insert a cotton swab into the colloid until a hard lump forms or resistance increases significantly. Use a ruler to measure the insertion depth D0. Calculate the ratio of the lump depth to the total depth: Sedimentation Degree D = (4-D0) / 4. A larger value indicates a poorer anti-settling effect. A sedimentation degree of 1 indicates complete sedimentation; a sedimentation degree of 0 indicates no sedimentation at all.]
[0050] *Note: The reason for recording the flow distance at 20 minutes is that a shorter time will result in larger errors or fail to reflect the differences between groups. A longer time will cause the flow distance of the experimental group with excellent fluidity to exceed the upper limit of the test mold. For the sedimentation test, a shorter or longer placement time will result in some experimental groups with similar sedimentation properties failing to reflect differences (either no sedimentation or all sedimentation).
[0051] Step 3: Prepare component B
[0052] Add 30 parts of polyetheramine curing agent and 10 parts of alicyclic amine curing agent into a planetary mixer, raise the temperature to above 80°C, add 5 parts of E51 epoxy resin, and carry out pre-reaction for 2 hours. Take a small amount of pre-reaction sample for infrared testing. If there is no obvious epoxy characteristic peak, it means that the pre-reaction process is completed; continue to add 0.5 parts of viscosity reducing agent, 2 parts of curing accelerator, 1.5 parts of thixotropic enhancer and 0.5 parts of defoaming agent, disperse evenly at high speed, and after no obvious particles are left, continue to add 4.5 parts of thixotropic powder and 46 parts of carbon black and physical filler, disperse at high speed and start vacuum defoaming to obtain component B.
[0053] Step 4: Mix component A and component B
[0054] Weigh component A and component B in a mass ratio of 3:1, mix them evenly by hand or mechanical stirring, and then they are ready for use.
[0055] Example 2
[0056] The preparation method of component A of this embodiment is as follows:
[0057] Add 20 parts of E51 epoxy resin and 0.5 parts of diluent into a planetary stirring kettle and mix evenly; then add 1 part of dispersant and 0.5 parts of defoamer, stir evenly at low speed, then add 78 parts of alumina, disperse evenly at low speed, then start high-speed stirring and start vacuum defoaming to obtain component A.
[0058] Component B of this embodiment is the same as component B of embodiment 1 and is also weighed according to a mass ratio of 3:1. It can be used after being mixed evenly by manual mixing or mechanical stirring.
[0059] Comparative Example 1
[0060] The 88 parts of aluminum oxide in component A of Example 1 were replaced with 88 parts of silicon dioxide, while the other ingredients remained unchanged.
[0061] Commercially available potting glue was purchased as Comparative Example 2 and Comparative Example 3:
[0062] Comparative Example 2: A150 two-component epoxy potting adhesive produced by Shenzhen Aosbon Co., Ltd.;
[0063] Comparative Example 3: CS2040 produced by Guangdong Shinaishi Industrial Co., Ltd.
[0064] The performance tests of the two-component high thermal conductivity epoxy potting adhesives prepared in Example 1 and Example 2, and Comparative Examples 1, 2, and 3 were conducted, and the results are as follows:
[0065]
[0066] It can be seen from the table that: compared with the various properties of common potting glues on the market, the use of the present invention to prepare alumina with a high filler ratio can not only greatly improve the thermal conductivity of the potting glue while basically maintaining the dielectric properties, but also greatly reduce the volume resistivity; although there is a certain loss in breaking strength, the elongation at break is also greatly improved, so that the potting glue has good flexibility and ductility after curing, which can not only improve the durability and reliability of the material, but also enrich the application scenarios of the product.
[0067] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiment. All technical solutions based on the concept of the present invention are within the scope of protection of the present invention. It should be noted that for those skilled in the art, various improvements and modifications that do not depart from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A high filler ratio two-component high thermal conductivity epoxy potting compound, characterized by: It is composed of independent component A and component B in a mass ratio of 2.5:1 to 3.5:1, wherein: Component A includes the following components by mass fraction: 9-28 parts of E51 epoxy resin, 0.3-0.7 parts of diluent, 70-90 parts of aluminum oxide, 0.8-1.2 parts of dispersant, and 0.3-0.7 parts of defoaming agent; Component B includes the following components by mass fraction: 27-33 parts of polyetheramine curing agent, 9-11 parts of alicyclic amine curing agent, 4.5-5.5 parts of E51 epoxy resin, 0.5-0.6 parts of viscosity reducer, 1.8-2.2 parts of curing accelerator, 1.4-1.6 parts of thixotropic enhancer, 0.5-0.6 parts of defoaming agent, 4.1-4.9 parts of thixotropic powder, 41.4-48.6 parts of carbon black and physical filler.
2. The high filler ratio two-component high thermal conductivity epoxy potting adhesive according to claim 1, characterized in that: The component A includes the following components by mass: 10 parts of E51 epoxy resin, 0.5 parts of diluent, 88 parts of aluminum oxide, 1 part of dispersant, and 0.5 parts of defoaming agent.
3. The high filler ratio two-component high thermal conductivity epoxy potting adhesive according to claim 1, characterized in that: The B component includes the following components by mass: 30 parts of polyetheramine curing agent, 10 parts of alicyclic amine curing agent, 5 parts of E51 epoxy resin, 0.5 parts of viscosity reducing agent, 2 parts of curing accelerator, 1.5 parts of thixotropic synergist, 0.5 parts of defoaming agent, 4.5 parts of thixotropic powder, 46 parts of carbon black and physical filler.
4. The high filler ratio two-component high thermal conductivity epoxy potting adhesive according to claim 1, characterized in that: The mass ratio of the component A to the component B is 3:
1.
5. The high filler ratio two-component high thermal conductivity epoxy potting adhesive according to claim 1, characterized in that: The dispersant is BYK-104S, BYK145 or BYK985; the defoamer is Deqian 6800 or BYK024.
6. The high filler ratio two-component high thermal conductivity epoxy potting adhesive according to claim 1, characterized in that: The alicyclic amine curing agent is an alicyclic diamine, and the viscosity reducing agent is BYK110.
7. The high filler ratio two-component high thermal conductivity epoxy potting adhesive according to claim 1, characterized in that: The curing accelerator is DMP30 or AEP; the thixotropic synergist is VA750B, BYK-R605 or BYK-R607.
8. The high filler ratio two-component high thermal conductivity epoxy potting adhesive according to claim 1, characterized in that: The thixotropic powder is H18 silica, M5 silica or organic bentonite, and the physical filler is heavy calcium carbonate.
9. A method for preparing a high filler ratio two-component high thermal conductivity epoxy potting compound, characterized by: The following steps are involved: 1) Preparation of component A: 1.1) Add 9-28 parts of E51 epoxy resin and 0.3-0.7 parts of diluent into a planetary stirred tank and mix well; 1.2) Add 0.8-1.2 parts of dispersant and 0.3-0.7 parts of defoamer and stir at low speed; 1.3) Add 70-90 parts of aluminum oxide, disperse evenly at low speed, then start high-speed stirring and start vacuum degassing to obtain component A; 2) Preparation of component B: 2.1) Add 27-33 parts of polyetheramine curing agent and 9-11 parts of alicyclic amine curing agent into a planetary mixer and heat to above 80°C; 2.2) Add 4.5-5.5 parts of E51 epoxy resin and perform a pre-reaction. Take a small amount of the pre-reaction sample for infrared testing. If there is no obvious epoxy characteristic peak, the pre-reaction process is complete. 2.3) After the pre-reaction process is completed, add 0.5-0.6 parts of viscosity reducing agent, 1.8-2.2 parts of curing accelerator, 1.4-1.6 parts of thixotropic synergist, and 0.5-0.6 parts of defoamer, and disperse at high speed until no obvious particles are left; 2.4) Add 4.1-4.9 parts of thixotropic powder and 41.4-48.6 parts of carbon black and body filler, disperse at high speed and start vacuum degassing to obtain component B 3) Weigh component A and component B according to a mass ratio of 2.5:1 to 3.5:1, mix them evenly by manual mixing or mechanical stirring, and then use.
Citation Information
Cited By
Self-leveling high-thermal-conductivity low-density two-component epoxy pouring sealant and preparation method thereof
CN121759130A